Formation of the Princely State of Jammu and Kashmir: The Historical Perspectives - Pir, Ali Mohd; Shiekh, Ab Rashid (SUSURGALUR, 2013)
ABSTRACT: The formation of the state of Jammu and Kashmir was unique as disparate territories stripped by the English East India Company from Sikh Kingdom of Punjab were brought together to form the state. The boundaries of the state were redrawn more for geo-political and administrative convenience rather than on a commonality shared by the people living there. Further, the heterogeneity of the state was the direct by-product of the military and diplomatic accomplishments of the founder of the Dogra dynasty, combined with the political acumen which completed the expansion of British power into northern India. This paper, however, attempts to discuss the historical background of the territories of Jammu, Kashmir, and Ladakh; and the processes and procedures which were involved in cobbling together of these disparate territories by the English East India Company and Raja Gulab Singh of Jammu to bring into being the princely state of Jammu and Kashmir. An attempt to highlight the polemic that followed the creation of this state is made to draw a conclusion regarding the handing over of Kashmir to Gulab Singh. The study attempts to examine the distinctive characteristics of the state of Jammu and Kashmir. KEY WORD: Princely state of Jammu and Kashmir, historical background, English East India Company, distinctive entities, and military and diplomatic accomplishments.IKHTISAR: Makalah ini berjudul âPembentukan Negara Kerajaan Jammu dan Kashmir: Perspektif Sejarahâ. Pembentukan negara bagian Jammu dan Kashmir adalah unik karena wilayah yang berbeda itu dilucuti oleh Perusahaan India Timur Inggris dari Kerajaan Sikh di Punjab untuk dibawa bersama dalam membentuk negara. Batas-batas negara digambar ulang lebih untuk kenyamanan geo-politik dan administratif daripada untuk kepentingan bersama oleh orang-orang yang tinggal di sana. Selanjutnya, heterogenitas negara adalah produk langsung dari prestasi militer dan diplomatik dari pendiri dinasti Dogra, dikombinasikan dengan kecerdasan politik untuk menyelesaikan perluasan kekuasaan Inggris ke India utara. Makalah ini, bagaimanapun, mencoba untuk membahas latar belakang sejarah dari wilayah Jammu, Kashmir, dan Ladakh; serta proses dan prosedur yang terlibat dalam pembentukan bersama dari wilayah-wilayah yang berbeda itu oleh Perusahaan India Timur Inggris dan Raja Gulab Singh dari Jammu agar menjadi negara kerajaan Jammu dan Kashmir. Sebuah usaha untuk menyoroti polemik yang diikuti pembentukan negara ini dibuat untuk menarik kesimpulan mengenai penyerahan Kashmir kepada Raja Gulab Singh. Penelitian ini bertujuan untuk menganalisis karakteristik khas dari negara bagian Jammu dan Kashmir.KATA KUNCI: Negara kerajaan Jammu dan Kashmir, latar belakang sejarah, Perusahaan India Timur Inggris, entitas khas, serta prestasi militer dan diplomatik.Â Â About the Authors: Ali Mohd Pir and Ab Rashid Shiekh are Ph.D. Students at the Centre of Advanced Study, Department of History AMU (Aligarh Muslim University) in Aligarh, Uttar Pradesh, India. For academic purposes, they can be reached via their e-mail address at: huzaifjhee@gmail.com and shiekhrashid.86@gmail.comHow to cite this article? Pir, Ali Mohd & Ab Rashid Shiekh. (2013). âFormation of the Princely State of Jammu and Kashmir: The Historical Perspectivesâ in SUSURGALUR: Jurnal Kajian Sejarah & Pendidikan Sejarah, Vol.1(2), September, pp.139-150. Bandung, Indonesia: Minda Masagi Press and UBD Bandar Seri Begawan, Brunei Darussalam, ISSN 2302-5808. Chronicle of the article: Accepted (June 28, 2013); Revised (August 3, 2013); and Published (September 30, 2013).